ANALISIS NILAI PERSEDIAAN AKHIR MENURUT STANDAR AKUNTANSI KEUANGAN ENTITAS TANPA AKUNTABILITAS PUBLIK PADA CV ZUL JAYA ABADI DI NUNUKAN - DENI DWI SAPUTRA; RANDE SAMBEN; RUSLIANSYAH - (Jurnal Ilmu Akuntansi Mulawarman (JIAM), 2016)
This study is based on the reality that there are unaccordance on scoring of inventory. Regarding this phenomenon the writer tried to find out the matters of it. By using the First In First Out Method in The Financial Accounting Standard Entities Without Public Accountability (SAK ETAP) in Chapter 11. The object of this research is CV Zul Jaya Abadi. The design of this study was descriptive qualitative in which the researcher conducted an analysis of comparison between The Financial Accounting Standard Entities Without Public Accountibility (SAK ETAP) in Chapter 11 which regulates the inventory with accounting treatment for inventory of CV Zul Jaya Abadi inventory scoring based on First In First Out (FIFO) method. Specifically, this study focused on the inventory of  CV Zul Jaya Abadi. To help researcher in the analyzing the data, the researcher used First In First Out system accordance The Financial Accounting Standard accountability (SAK ETAP) in Chapter 11. Based on the cost method of inventory scoring First In First Out (FIFO), between The Financial Accounting Standard Entities without Public Accountibility (SAK ETAP) and the company it was found that there is the difference of ending inventory. This is because the company's cost of sales charge Last In Fisrt Out method, thus causing the difference between the value of ending inventory. It influenced to The Statement of Financial Position (Balance Sheet) in 2015 and the inventory beginning in next year and it influenced to The Income Statement and Cost of Sales which impacting net income before and after taxes. Thus it can be concluded that the scoring inventory which implemented by CV Zul Jaya Abadi is not accordance with The Financial Accounting Standard Entities without Public Accountability (SAK ETAP) in Chapter 11.Keywords: Inventory, SAK ETAP, Scoring Inventory